GLP-1/dexamethasone inhibits food reward without inducing mood and memory deficits in mice. (June 2019) - Décarie-Spain, Léa; Fisette, Alexandre; Zhu, Zhimeng; Yang, Bin; DiMarchi, Richard D.; Tschöp, Matthias H.; Finan, Brian; Fulton, Stephanie; Clemmensen, Christoffer
Abstract: Background: Pharmacotherapies targeting motivational aspects of feeding and palatable food reward, while sparing mood and cognitive function, represent an alluring approach to reverse obesity and maintain weight loss in an obesogenic environment. A novel glucagon-like peptide-1/dexamethasone (GLP-1/Dexa) conjugate, developed to selectively activate glucocorticoid receptors in GLP-1 receptor-expressing cells was shown to decrease food intake and lower body weight in obese mice. Here, we investigate if this novel drug candidate modulates the rewarding properties of food and if it affects behavioral indices of mood and memory. Methods: C57Bl6 mice treated with the GLP-1/Dexa conjugate, GLP-1 or vehicle lever-pressed for high-fat, high sugar (HFHS) food rewards in an operant task. Alterations in food-motivated behavior were also assessed following a HFHS diet withdrawal manipulation (switch to chow). The effects of repeated GLP-1/Dexa conjugate, GLP-1 or vehicle on free-feeding intake, body weight, anxiodepressive behaviors (elevated-plus maze, open field test & forced swim test), memory (novel object recognition) and mRNA expression of reward-relevant markers in the nucleus accumbens were also evaluated in mice fed a HFHS diet for 12 weeks. Results: Mice treated with a GLP-1 analogue displayed a transient (4 h) reduction in their motivation to lever press for HFHS reward, whereas treatment with equimolar doses of GLP-1/Dexa delivered a superior and sustained (20 h) suppression of food-motivated behavior. GLP-1/Dexa also inhibited food reward following withdrawal from the HFHS diet. These benefits coincided with related transcriptional changes of dopaminergic markers in the nucleus accumbens. Importantly, repeated GLP-1/Dexa treatment during a HFHS diet caused weight loss without affecting anxiodepressive behavior and memory. Conclusion: Via its actions to blunt the rewarding effects of palatable food without affecting mood and recognition memory, GLP-1-directed targeting of dexamethasone may serve as a promising and safe anti-obesity strategy. Highlights: GLP-1/Dexamethasone (GLP-1/Dexa) is a new pre-clinical anti-obesity drug candidate. GLP-1/Dexa suppresses food-motivated behaviors in mice. GLP-1/Dexa induces changes in reward-relevant markers in the nucleus accumbens. GLP-1/Dexa has no adverse effect on anxio-depressive behavior and recognition memory.